Interactive Powerpoint Media as an Effort to Improve Student Learning Outcomes in Mathematics Learning at MI Miftahul Hidayah - Kusnul Masurin; Lailatul Munawaroh (Journal of Action Research in Islamic Education, 2025)
This research aims to enhance student learning outcomes in Islamic Religious Education by utilizing interactive PowerPoint as a teaching tool. The study employs a classroom action research (CAR) design consisting of four stages: planning, implementation, observation, and reflection. The participants in this study were elementary school students. Data were collected through tests and observation methods. Tests were used to assess student learning outcomes, while observations focused on evaluating the learning activities of both teachers and students. The data analysis was conducted using descriptive statistical techniques, comparing the results with predetermined success indicators. The findings reveal that the use of interactive PowerPoint effectively improves students’ learning outcomes in Islamic Religious Education. This is evidenced by the increasing percentage of students achieving mastery: 56.71% in the pre-cycle, 75.39% in the first cycle, and 93.96% in the second cycle. These results suggest that interactive PowerPoint can serve as a valuable alternative to enhance student performance in Islamic Religious Education classes.